Urban Resilience: How to Apply in the Planning and Design Practice? - Novi Maulida Ni’mah; Bakti Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The topic of urban resilience has been gain much interest in the field of sustainability yet the use of the concept particularly for urban planning and design is still in debate. This paper searches for the gap in the use of the urban resilience concept for planning and design practice. The resilience terminology itself emerges and is known from the socio-ecological perspective, therefore the development of the terminology into the built environment issue needs to be appropriately translated. This paper aims to explore the advocacy of how urban resilience should be put into the discourse of planning and design practice, especially the standing of the concept within planning theory. The study is conducted through a literature review with objectives among others: (1) to get insight into what is urban resilience concept and how it has been used in the context of the urban and regional system? and (2) to elaborate on the potential of urban resilience concept be used in the planning and design practice through the perspective of planning theory. The initial result of the study concludes that the urban resilience concept has the potential to reframe the perspective of planning theory that has been applied nowadays, particularly the theory of planning and theory in planning with the emergence of so-called transformative and recovery planning. Both planning approaches must be considered the urban system as the object of planning.